A AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL UMBI PORANG (Amorphophallus oncophyllus) DENGAN METODE EKSTRAKSI ULTRASONIK - Nur Rahmadani Hartaman (PHARMACY UMI JOURNAL SYSTEM, 2023)
Porang tuber (Amorphophallus oncophyllus) is a tuber plant belonging to the Araceae family and Monocotyledoneae class, has benefits as an antihyperglycemic, antihypertensive, antihyperlipidemic, antibacterial and antioxidant. Porang tubers contain several compounds such as terpenoids, flavonoids, alkaloids, saponins and tannins. This study aims to determine the potential antioxidant activity of the ethanol extract of porang tuber (Amorphophallus oncophyllus) using the DPPH free radical scavenging method. The extraction method used was ultrasonic with 96% ethanol solvent to obtain a viscous extract of 4.033 grams. The test was carried out quantitatively by measuring the absorbance at the maximum wavelength of 516 nm using a UV-Vis spectrophotometer with quercetin as a standard. The results showed that the regression value for the quercetin comparator was y = 3.1303x + 0.2292 with an R2 value = 0.9974 and an IC50 value of 15.899 (μg/mL) while the antioxidant activity of the ethanol extract of porang tuber (Amorphophallus oncophyllus) obtained a regression value of y = 0.5217x– 9.5416 with an R2 value = 0.9915 and an IC50 value of 114.129 (μg/mL). The results of this study indicate that the ethanol extract of Porang tuber (Amorphophallus oncophyllus) has an antioxidant effect in the moderate category.